Acinic cell carcinoma of the parotid gland in children: a case report and literature review. - Michail, P; Karavokyros, I; Pikoulis, E; Arvelakis, A; Charminis, G; Michail, O; Theodoros, D (West Indian Med J, 2008)
Parotid acinic cell carcinoma is a rare malignancy in childhood. We report the case of a 12-year-old girl presenting with a palpable mass in the left maxillofacial area. The radiologic evaluation showed a parotid mass. Tumour resection revealed acinic cell carcinoma of the parotid gland. She underwent complementary total parotidectomy without any adjuvant treatment. The patient has been disease-free for the last five years. We review the literature on acinic cell carcinomas of parotid glands in childhood.
Keywords: Carcinoma, Acinar Cell; Child; Female; Humans; Oral Surgical Procedures; Parotid Neoplasms